2020
DOI: 10.11604/pamj.2020.37.258.16929
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risk markers among stroke out-patients at the neurology clinic of a teaching hospital in Ghana

Abstract: Introduction stroke survivors are at risk of malnutrition due to inadequate dietary intake, as a result of neurological disorders causing dysphagia, depression and impaired ability to self-feed. There is paucity of information on nutritional status of stroke survivors after discharge from hospital care, hence, this study sought to determine the nutritional risk markers among stroke out-patients at the Neurology Clinic of Komfo Anokye Teaching Hospital, Kumasi, Ghana. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…19 One possible explanation is that, as UA has been found useful as a biochemical indicator to determine the nutritional status of stroke survivors, AIS patients may be at risk of malnutrition due to decreased UA caused by dysphagia and impaired self-eating ability. 36 This is because dietary factors can affect serum levels by providing purines as precursors of uric acid, affecting nucleotide conversion, or affecting its excretion. 37 Moreover, as the antioxidant capacity of UA has been established, 38 a low UA level reflects insufficient ability to resist oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…19 One possible explanation is that, as UA has been found useful as a biochemical indicator to determine the nutritional status of stroke survivors, AIS patients may be at risk of malnutrition due to decreased UA caused by dysphagia and impaired self-eating ability. 36 This is because dietary factors can affect serum levels by providing purines as precursors of uric acid, affecting nucleotide conversion, or affecting its excretion. 37 Moreover, as the antioxidant capacity of UA has been established, 38 a low UA level reflects insufficient ability to resist oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of raw materials for the formation of skeletal muscle will not only affect the degree of functional recovery but also affect the expression of plasticity genes in the brain recovery mechanism after stroke. [19,20] Yoshimura et al [21] found that lower Hb was closely related to the severity of sarcopenia, recovery of physical function, and swallowing function in the rehabilitation cohort after stroke. The European Society for Parenteral and Enteral Nutrition [22] proposed a professional consensus that malnutrition is widely involved in the pathogenesis of nervous system diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Malnutrition is common in stroke patients, and its causes are directly related to neurological diseases, such as cognitive and consciousness disorders, www.md-journal.com neurogenic vomiting, neurogenic dysphagia, depression, motor disorders and gastrointestinal dysfunction. [19,20] Older adults, including those after stroke, often suffer from malnutrition, which has a negative impact on their physical function, strength and the independence of their daily life. [21] Changes in nutritional status of stroke patients, such as insufficient intake and excessive nutritional consumption, will lead to a decrease in muscle synthesis and promote the occurrence of sarcopenia.…”
Section: Observationsmentioning
confidence: 99%